From Public Health Policy to Impact for COVID-19: A Multi-Country Case Study in Switzerland, Spain, Iran and Pakistan - Maryam Tavakkoli; Maryam Tavakkoli; Aliya Karim; Aliya Karim; Fabienne Beatrice Fischer; Fabienne Beatrice Fischer; Laura Monzon Llamas; Azam Raoofi; Azam Raoofi; Shamsa Zafar; Carmen Sant Fruchtman; Carmen Sant Fruchtman; et al. (International Journal of Public Health, 2022)
Objectives: With the application of a systems thinking lens, we aimed to assess the national COVID-19 response across health systems components in Switzerland, Spain, Iran, and Pakistan.Methods: We conducted four case studies on the policy response of national health systems to the early phase of the COVID-19 pandemic. Selected countries include different health system typologies. We collected data prospectively for the period of January–July 2020 on 17 measures of the COVID-19 response recommended by the WHO that encompassed all health systems domains (governance, financing, health workforce, information, medicine and technology and service delivery). We further monitored contextual factors influencing their adoption or deployment.Results: The policies enacted coincided with a decrease in the COVID-19 transmission. However, there was inadequate communication and a perception that the measures were adverse to the economy, weakening political support for their continuation and leading to a rapid resurgence in transmission.Conclusion: Social pressure, religious beliefs, governance structure and level of administrative decentralization or global economic sanctions played a major role in how countries’ health systems could respond to the pandemic.